May days in Hong Kong : riot and emergency in 1967 - Bickers, Robert A.; Yep, Ray, 1964- (UPCC book collections on Project MUSE., 2009)
In this study of the anti-colonial riots which erupted in Hong Kong in May 1967, the authors of May Days in Hong Kong shed new light on their causes, their impact on future government policy and on Sino-British relations, and their legacy for Hong Kong society and governance, and the people of the territory. This is the first sustained exploration of the anti-colonial campaign that was inspired by the Cultural Revolution in China, recent events in Macau, and fuelled by inequalities in Hong Kong society. The riots presented a sustained challenge to British authority. As leftist-led demonstration.